Constructing place and space in the design of learning environments for PBL in Malaysian universities - M.M. Tahir,; N.A.G. Abdullah,; I.M.S. Usman,; A.I. Che Ani,; M.F.I. Mohd Nor,; M.Surat, (Penerbit Universiti Kebangsaan Malaysia, 2009)
Malaysia’s provisional entry into the Washington Accord has resulted in an overhaul of engineering education in this country. Gone are the days of traditional teaching in engineering. A myriad of changes have been introduced including changes in attitudes, orientation, curriculum, and delivery, to name a few. One important aspect that architects and planners have neglected is in the area of educational infrastructure, namely the place and space of the learning environment. The advent of new teaching methods has brought with it different infrastructural needs. Problembased learning (PBL) is achieving great currency in engineering education these days. However, the present-day teaching-learning environment is seen as defective: it does not provide optimum learning in the PBL context. This paper attempts to reconsider the relationship of physical settings to the student learning experience. This paper will also look at the problems of place and space in the engineering education in Universiti Kebangsaan Malaysia, with a comparison made with the integrated architectural program, and provide examples of the environmental design that would be conducive to PBL